EFFECT OF STOICHIOMETRIC COMPOSITIONS ON THE DEVELOPMENT OF PHASE AND MICROSTRUCTURE IN CALCIA STABILIZED ZIRCONIA CERAMIC - Durrani, S. K.; Qureshi, A. H.; Naz, S.; Hussain, S. Z.; Arif, M.; Iqbal, M. (The Nucleus, 2013)
Calcia stabilized zirconia (CSZ) ceramic material was synthesized with stoichiometric compositions 4, 8, 12 and 16wt.% by mixed oxide reaction using fine homogeneous salts of zirconia and calcia. Powder compacts were sintered at 1950Â°C for 6h in an inert argon atmosphere. The phase identification, purity, crystalline and lattice parameters of cubic CSZ were measured by X-ray diffraction (XRD). Combination of cubic zirconia (Ca0.15Zr0.85O1.85), calcium-zirconium oxide (CaZrO3) and zirconium oxide (ZrO) phases were observed in all compositions. The percent relative densities were measured in order to evaluate the material performance and found to decrease from 85 to 74% with increase of stoichiometeric compositions 4 to 16wt%. These results were in agreement with scanning electron microscopy (SEM) where it was observed that porosity increased with increase of calcia. The co-efficient of thermal expansion was estimated by dilatometry. The results revealed that coefficient of thermal expansion (Î±) decreases with the increase of compositions from 4 to 16wt.% .